2008
DOI: 10.1101/lm.970408
|View full text |Cite
|
Sign up to set email alerts
|

Training with inedible food in Aplysia causes expression of C/EBP in the buccal but not cerebral ganglion

Abstract: Training with inedible food in Aplysia increased expression of the transcription factor C/EBP in the buccal ganglia, which primarily have a motor function, but not in the cerebral or pleural ganglia. C/EBP mRNA increased immediately after training, as well as 1–2 h later. The increased expression of C/EBP protein lagged the increase in mRNA. Stimulating the lips and inducing feeding responses do not lead to long-term memory and did not cause increased C/EBP expression. Blocking polyADP-ribosylation, a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 51 publications
5
41
1
Order By: Relevance
“…[45][46][47][48] In Aplysia, gene expression and protein synthesis after training are necessary for long-term LFI memory. 32,49,50 To determine whether the effect of sleep deprivation on the consolidation of memory is phylogenetically conserved, animals were trained at ZT 11 during the late day, sleep deprived for the first 9 h of the night (ZT 12-ZT 21), and then tested for LTM 24 h after training. Sleep deprivation after training impaired LTM as sleep deprived animals had response times significantly greater than non-sleep deprived control animals ( Figure 2A; Figure S1C).…”
Section: Sleep Deprivation Blocks the Consolidation Of Ltmmentioning
confidence: 99%
“…[45][46][47][48] In Aplysia, gene expression and protein synthesis after training are necessary for long-term LFI memory. 32,49,50 To determine whether the effect of sleep deprivation on the consolidation of memory is phylogenetically conserved, animals were trained at ZT 11 during the late day, sleep deprived for the first 9 h of the night (ZT 12-ZT 21), and then tested for LTM 24 h after training. Sleep deprivation after training impaired LTM as sleep deprived animals had response times significantly greater than non-sleep deprived control animals ( Figure 2A; Figure S1C).…”
Section: Sleep Deprivation Blocks the Consolidation Of Ltmmentioning
confidence: 99%
“…We have reported that, after training with inedible food, ApC/EBP is transcribed and translated in the buccal ganglia (Levitan et al 2008). A subsequent study also localized the expression of MAP kinase after training to the buccal ganglia (Michel et al 2011).…”
Section: Apc/ebp Expression Is Present In Mechanoafferent Neuronsmentioning
confidence: 84%
“…Attempts to swallow repeatedly fail, and the animals learn to stop responding (Susswein et al 1986;Schwarz et al 1988Schwarz et al , 1991Botzer et al 1998;Katzoff et al 2002Katzoff et al , 2006Katzoff et al , 2010Cohen-Armon et al 2004;Levitan et al 2010;Michel et al 2010Michel et al , 2011. Previous studies (Levitan et al 2008;Michel et al 2011Michel et al , 2012 used molecular markers of memory to localize the learning to specific ganglia. After training with inedible food, the markers were found in the buccal, but not in the cerebral, pleural, or pedal ganglia of Aplysia (Levitan et al 2008;Michel et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, hippocampal circadian rhythms in CREB activation have been shown to be dependent upon the Period1 gene (Rawashdeh et al 2014). In Aplysia, training animals during the subjective day results in significantly increased protein levels of the CREBdependent immediate early gene ApC/EBP (Lyons et al 2006), a transcription factor in nonassociative (Alberini et al 1994), and associative memory formation (Levitan et al 2008). In Drosophila mushroom bodies, a region necessary for many forms of memory, dCREB2 exhibits circadian oscillations in gene expression, nuclear protein levels and activity, likely mediating rhythms in LTM formation (Tanenhaus et al 2012;Fropf et al 2014).…”
Section: Micementioning
confidence: 99%